An Investigating Students’ Experiences of Autonomous Learning In English Online Platform - Rilvina Hildayati; Melyann Melani (The Progress: Journal of Language and Ethnicity, 2023)
In the 21st century, autonomy in learning has become a primary objective for students. Students should take responsibility for their own learning in order to increase their interest in learning English. One popular English teaching medium in the present day is the English Online Platform, which supports students in autonomous learning by providing a source of learning materials and facilitating the expansion of their English knowledge, among other benefits. This study aims to examine students' experiences of autonomous learning using the English Online Platform through a quantitative technique and questionnaire design. The results of this study indicate that the students included in the research possess a clear understanding of the potential benefits of autonomous learning. Therefore, the utilization of the English Online Platform can serve as a learning tool to enhance students' autonomous learning.